Characteristics of type ii diabetes mellitus patients at trading general hospital, Simalungun regency - Shofian Syarifuddin; Chika Ade Hendranti (Institute of Computer Science (IOCS), 2022)
Complications caused by diabetes are becoming a more serious problem so controlling blood glucose intensively can reduce diabetes mortality by reducing complications that arise. This study aims to determine the characteristics of Type II Diabetes Mellitus Patients at the Trade Area General Hospital, Simalungun Regency in 2016. With this type of descriptive research, this research was carried out at the Trade Area General Hospital, Simalungun Regency from July to September 2016 with a total population of 40 people using the following techniques: sampling, namely total sampling where all the population is used as a sample. The results of this study indicate that the younger a person has diabetes mellitus, the less the number of diabetes mellitus sufferers, the greater the number of diabetes mellitus sufferers by women, there are fluctuations in the duration of the disease in the Toba and Simalungun tribes, while the Javanese suffer longer. diabetes mellitus, the incidence rate has decreased. The duration of the disease with adherence to taking medication did not have a significant difference compared to the duration of the disease with adherence to diet. The duration of the disease with dietary adherence is a significant difference between adherents and non-adherents, where the tendency is not to comply with dietary rules. It is hoped that Efarina University through the Bachelor of Nursing study program can provide counseling about Diabetes Mellitus, specifically Type II Diabetes Mellitus, both in the community and in hospitals. It is recommended that the hospital pay more attention to the diet of patients with Type II Diabetes Mellitus and the administration of dict according to the portion and condition of the patient in this study can be explored by the information that has been conveyed by researchers regarding Type II Diabetes Mellitus sufferers.